2013
DOI: 10.1007/s10545-012-9576-9
|View full text |Cite
|
Sign up to set email alerts
|

High risk of primary liver cancer in a cohort of 179 patients with Acute Hepatic Porphyria

Abstract: Acute hepatic porphyria carries a high risk of primary liver cancer above the age of 50 which warrants ultrasound surveillance. Sex distribution and frequency of cirrhosis differs from more common aetiologies of primary liver cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 24 publications
6
89
3
Order By: Relevance
“…Later, the same group reported on 22 patients with AIP and HCC (Innala and Andersson 2011). Recently, Sardh et al detected 23 primary liver tumours in patients with AHP (Sardh et al 2013). An overview of the major studies on the concomitant occurrence of HCC and AHP is given in Table 2.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Later, the same group reported on 22 patients with AIP and HCC (Innala and Andersson 2011). Recently, Sardh et al detected 23 primary liver tumours in patients with AHP (Sardh et al 2013). An overview of the major studies on the concomitant occurrence of HCC and AHP is given in Table 2.…”
Section: Discussionmentioning
confidence: 98%
“…Since the first report on the concomitant occurrence of HCC and AIP in 1984, several studies have shown an association between this type of primary liver cancer and the AHPs in Europe (Lithner and Wetterberg 1984;Hardell et al 1984;Bengtsson and Hardell 1986;Tidman et al 1989;Grabczynska et al 1996;Andersson et al 1996;Linet et al 1999;Andant et al 2000;Schneider-Yin et al 2009;Innala and Andersson 2011;Elder et al 2013;Sardh et al 2013). However, some of the aforementioned studies linking HCC to AHP certainly include cases in which there were further risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients lead a normal life and seldom have attacks. However, both symptomatic and latent patients have an increased risk of chronic renal failure with progressive tubulointerstitial nephropathy [27] and hepatocellular carcinoma (HCC) [28]. The significant association between AHP and HCC without underlying liver disease became an important issue [29].…”
Section: Specific Treatmentmentioning
confidence: 99%
“…Recurrent severe attacks are rare and affect about 5% of patients with acute porphyria; typically recurrent attacks occur in women in association with the menstrual cycle and usually improve after the menopause. Severe attacks may occur more frequently than monthly and can be associated with progressive neuropathy, chronic pain, renal impairment and increased risk of hepatocellular carcinoma (Sardh et al 2013). Frequent attacks result in severe disability, making normal working, family and social life very difficult.…”
Section: Introductionmentioning
confidence: 99%